Imobilização da enzima frutosiltransferase extracelular de Aspergillus oryzae IPT-301 em sílica-gel para produção de frutooligossacarídeos - Faria, Larissa Lemos (2019)
Fructooligosaccharides (FOS) are low-calorie prebiotic sugars that present several benefits for human health. There is a growing interest in the application of FOS as substitute for conventional sweeteners, which makes it necessary to develop processes, in industrial-scale, for the production of these components, developed in Brazil. They are produced by transfructosylation reaction of sucrose, catalyzed by microbial enzymes such as fructosyltransferase (FTase E.C.2.4.1.9), from Aspergillus oryzae IPT-301. Thus, the present work focused on the studies of the immobilization process of the enzyme extracellular microbial FTase, using silica gel as support, for the production of FOS. For this purpose, immobilization tests were performed, by physical adsorption, at different temperatures (20 ° C, 25 ° C, 30 ° C and 35 ° C) for 6 hours, with agitation of 175 rpm, 10 mL fermented broth pH 5.5, containing the extracellular microbial enzyme, and 1.0 g of silica gel. After obtaining the adsorption kinetic profiles, a central composite design (CCD) 2² was performed, varying the temperature and pH of the reaction medium, in order to define the optimal reaction conditions for the immobilized enzyme. Besides these studies, to characterize the immobilized biocatalyst, tests were carried out for stability to pH, thermal stability, evaluation of the influence of substrate concentration on the enzymatic reaction and operational stability tests. The kinetic immobilization profiles indicated that the transfructosylation activity (AT), present in the fermented broth, decreased with the increase of the immobilization time and that the highest immobilization yield, about 85% was obtained for an immobilization temperature of 35 °C. From the experimental design, it was possible to define the optimal reaction conditions for the immobilized enzyme, obtaining pH and temperature values of 5.5 and 50ºC, respectively. The evaluation of the substrate concentration indicated that the best conditions for the enzymatic reaction were reached for sucrose concentrations between 400 and 600 g.L-1 and enzymatic kinetics were better fitted to the cooper Hill model. In addition, pH stability assays showed that the immobilized enzyme was stable (relative to about 100%) in the pH range of 5.0 to 6.5 and the thermal stability analysis showed, by means of the thermodynamic parameters evaluated, that immobilization provided an increase in energy required for enzymatic deactivation, increasing its thermostability, so as to increase the half-life of the FTase enzyme immobilized at 2.5 times relative to the biocatalyst in its free form. From the operational stability tests, it was verified that the enzyme can be reused for 2 consecutive batch cycles without loss of activity. By characterizing the silica gel support, it was possible to prove the adsorption of the enzyme on its surface. Therefore, from the immobilization and characterization studies it was possible to conclude that extracellular FTase was satisfactorily immobilized on silica gel.